Efficacy of in situ replacement of a tunneled cuffed catheter in patient receiving chronic hemodialysis - YUAN Li-ping; LUO Min-hong; CHEN Zhen-wei; CHEN Qiu-lian; WU Qiang; Yang Tie-cheng (Linchuang shenzangbing zazhi)
Objective To explore the efficacy of in situ replacement of a tunneled cuffed catheter(TCC) by comparing with the method of re-catheterization of TCC in a separate site in chronic hemodialysis patients.Methods A total of 28 patients receiving chronic hemodialysis with dysfunctional TCCs 2 years after catheterization were included in this study.All participants received a new TCC insertion by the method of re-catheterization of the TCC in a separate site(n = 16) or replacement of the TCC in situ(n= 12).Efficacy of indwelling TCCs,complications related to insertion,and patients’ characteristics were compared in these two groups of patients by the different method of catheterization.Results Six cases of failing to insert a TCC were seen in patients who received re-catheterization of TCC in a separate site(6/16).In patients who received replacement of TCC in situ,all insertions were successful with catheter blood flow more than 220 ml/min and without any complication.There was no statistically significant difference in catheter blood flow,Kt/V,URR,dialysis duration,and patients’ demographics between these two groups of patients with different catheterization methods.After a 3-month follow-up,the rate of catheter related infection after insertion was higher in patients who received replacement TCC in situ than those who received re-catheterization of TCC in a separate site(P<0.05).Conclusions In situ replacement of a TCC is an efficient method to treat a dysfunctional catheter in patients on chronic hemodialysis.Caution should be taken to reduce the rate of infection during catheterization.